Mapping of multi-elements during melting and solidification using synchrotron X-rays and pixel-based spectroscopy. - Liotti, E; Lui, A; Connolley, T; Dolbnya, I; Sawhney, K; Malandain, A; Wilson, M; Veale, M; Seller, P; Grant, P (Nature Publishing Group, 2015)
A new synchrotron-based technique for elemental imaging that combines radiography and fluorescence spectroscopy has been developed and applied to study the spatial distribution of Ag, Zr and Mo in an Al alloy during heating and melting to 700, and then re-soldification. For the first time, multi-element distributions have been mapped independently and simultaneously, showing the dissolution of Ag- and Zr-rich particles during melting and the inter-dendritic segregation of Ag during re-solidification. The new technique is shown to have wide potential for metallurgical and materials science applications where the dynamics of elemental re-distribution and segregation in complex alloys is of importance.